Three‐point stapled fixation technique to manage ileostomy spout retraction. Issue 4 (7th March 2019) - Behrenbruch, Corina; Carr, Gareth; Johnston, Michael; Woods, Rodney
Abstract : This paper details a technique to manage non‐fixed stomal retraction using a using a non‐cutting linear stapler.